Book Review - Oliveira, Eduardo (Border Crossing, 2016)
Evinç Doğan (2016). Image of Istanbul, Impact of ECoC 2010 on The City Image. London: Transnational Press London. [222 pp, RRP: £18.75, ISBN: 978-1-910781-22-7] The idea of discovering or creating a form of uniqueness to differentiate a place from others is clearly attractive. In this regard, and in line with Ashworth (2009), three urban planning instruments are widely used throughout the world as a means of boosting a city’s image: (i) personality association - where places associate themselves with a named individual from history, literature, the arts, politics, entertainment, sport or even mythology; (ii) the visual qualities of buildings and urban design, which include flagship building, signature urban design and even signature districts and (iii) event hallmarking - where places organize events, usually cultural (e.g., European Capital of Culture, henceforth referred to as ECoC) or sporting (e.g., the Olympic Games), in order to obtain worldwide recognition.